2024
DOI: 10.1002/pei3.10139
|View full text |Cite
|
Sign up to set email alerts
|

Fern mycorrhizae do not respond to fertilization in a tropical montane forest

Thais Guillen,
Michael Kessler,
Jürgen Homeier

Abstract: Ferns are known to have a lower incidence of mycorrhization than angiosperms. It has been suggested that this results from carbon being more limiting to fern growth than nutrient availability, but this assertion has not been tested yet. In the present study, we took advantage of a fertilization experiment with nitrogen and phosphorus on cloud forest plots of the Ecuadorean Andes for 15 years. A previous analysis revealed changes in the abundances of fern species in the fertilized plots compared to the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(130 reference statements)
0
0
0
Order By: Relevance
“…When we considered just the Swiss populations, we found that the composition of AMF communities linked to S. spicant was mainly influenced by light, soil C and N, and soil pH. Together, this reveals a very low specificity of fungal partners in fern species, coinciding with previous findings ( Perez-Lamarque et al., 2022 ; Guillen et al., 2024 ; Guillen-Otero et al., 2024 ). For instance, a regional study of Botrychium lunaria (Ophioglossaceae) in the Swiss Alps, found that the composition of the AMF community associated was significantly impacted by soil pH and humus cover but was not predicted by them ( Sandoz et al., 2020 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…When we considered just the Swiss populations, we found that the composition of AMF communities linked to S. spicant was mainly influenced by light, soil C and N, and soil pH. Together, this reveals a very low specificity of fungal partners in fern species, coinciding with previous findings ( Perez-Lamarque et al., 2022 ; Guillen et al., 2024 ; Guillen-Otero et al., 2024 ). For instance, a regional study of Botrychium lunaria (Ophioglossaceae) in the Swiss Alps, found that the composition of the AMF community associated was significantly impacted by soil pH and humus cover but was not predicted by them ( Sandoz et al., 2020 ).…”
Section: Discussionsupporting
confidence: 85%
“…For instance, a regional study of Botrychium lunaria (Ophioglossaceae) in the Swiss Alps, found that the composition of the AMF community associated was significantly impacted by soil pH and humus cover but was not predicted by them ( Sandoz et al., 2020 ). A study analyzing the response of AMF associated with two epiphytic and two terrestrial fern species to 15 years of N and P fertilization in Ecuador also showed that fertilization did not determine the composition of the fungal assemblages ( Guillen et al., 2024 ). Random variation in the community composition might be introduced by taxon-specific constraints on dispersal (e.g., variations in the size and shape of the spores) and colonization processes at a regional scale ( Bahram et al., 2015 ; Lekberg et al., 2024 ).…”
Section: Discussionmentioning
confidence: 99%